Bat-eared foxes Otocyon megalotis as predators of harvester termites Hodotermes mossambicus in the Orange Free State - Mackie, Alastair James (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1988.